Adrenal suppression in children treated with swallowed fluticasone and oral viscous budesonide for eosinophilic esophagitis. Issue 1 (December 2016) - Ahmet, Alexandra; Benchimol, Eric; Goldbloom, Ellen; Barkey, Janice
Abstract Background Adrenal suppression (AS), a glucocorticoid (GC) side effect associated with significant morbidity, is well described related to inhaled corticosteroid therapy for asthma. Swallowed topical glucocorticoid therapy is the main pharmacotherapy treatment for eosinophilic esophagitis (EoE) and therefore children with EoE are potentially at increased risk of AS. Methods In this prospective cohort study, we included children and youth <18 years diagnosed with EoE and treated with swallowed fluticasone or oral viscous budesonide for more than 1 month. First morning cortisol and low dose adrenocorticotropic hormone stimulation test (LDST) were performed 2 weeks following GC discontinuation. AS was defined as an abnormal LDST result (cortisol peak <500 nmol/L). We determined the prevalence and duration of AS related to swallowed topical GC therapy in EoE by LDST, as well as the diagnostic accuracy of first morning cortisol compared to LDST. Results Of 29 participants enrolled, 26 (89.7 %) received oral viscous budesonide and 3 (10.3 %) received swallowed fluticasone. Nineteen (65.5 %) participants had AS. Median duration of AS was 43 weeks. Five (17.2 %) participants had persistent AS at 12 months. There were no identifiable risk factors for the development of AS. First morning cortisol was highly specific but had poor sensitivity for detection of AS. Conclusions The majority of children with EoE had AS after discontinuation of swallowed topical GC therapy. Stress steroids should be considered in children treated with swallowed topical GC therapy for EoE, even after GC discontinuation, to prevent possible adrenal crisis.